Implementasi Program Daily Report dalam Pendidikan Karakter Peserta Didik: Implementation of the Daily Report Program in Character Education for Students - Elfa Nopiana Rahmah; Nashrullah KMR, Galuh; Arifin, M. Fahmi (ISEDU : Islamic Education Journal, 2025)
This research aims to describe and analyze the implementation of the daily report program in the character education of students at the Ukhuwah Integrated Islamic Elementary School, Banjarmasin, to describe and analyze the implications of the daily report program in the character education of students at the Ukhuwah Integrated Islamic Elementary School, Banjarmasin. This research uses a qualitative approach with a case study type of research. The subjects in this research were the principal, head of curriculum, homeroom teacher, class assistant and students, while the object studied was the daily report program. The data collection techniques used in this research were observation, interviews and documentation. The data analysis technique used is data reduction, presentation of verification data. Researchers used sub-triangulation and technical triangulation to obtain data validity. Based on the research results, it can be concluded that the implementation of the daily report program in the character education of students at the Ukhuwah Banjarmasin Integrated Islamic Elementary School is very supportive of character education, the daily report is carried out through habituation carried out by students, the daily report is carried out at school and at home supported by books. liaison. Meanwhile, the implication of the daily report is that it can increase positive behavior and reduce negative behavior of students. With the daily report, students will certainly make more positive habits.